THE EFFECT OF CURRENT RATIO AND DEBT TO EQUITY RATIO ON PROFIT GROWTH IN CIGARETTE COMPANIES THAT GO PUBLIC 2017-2022 PERIOD - Ricardo Rafael Laurensius Gultom; Ari Sulistyowati; Christoporus Indra Wahyu; Tyna Yunita (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This study aims to determine and analyze the effect current ratio, debt to equity ratio, on profit growth in cigarette companies listed on the Indonesia Stock Exchange for the 2017-2022 period. This research was conducted using a quantitative research approach. The total population in this study amounted to 5 companies. The sample was selected using a saturated sampling technique, in order to obtain a sample of 5 companies. The data used in this study is secondary data collected through annual financial reports accessed from idx.co.id which is the research sample. The analytical method used in this research is multiple linear regression analysis. The data was tested using the Eviews12 application. Based on the results of the influence test current ratio on profit growth obtained test results with a probability of 0.1235> 0.05 which means that (X1) CR partially does not affect profit growth. Test results debt to equity ratio has a probability of 0.0000 <0.05 which means that (X2) DER partially has a positive effect on profit growth. And (X1) Current ratio ,(X2) Debt to equity ratio simultaneously affect the profit growth